(untitled) - Prof. Dr. Thomas Steger (Editor-in-chief), University of Regensburg; Prof. Dr. Rainhart Lang, Chemnitz University of Technology; Tiia Vissak, University of Tartu (JEEMS Journal of East European Management Studies, 1998)
The Journal of East European Management Studies aims to promote dialogue and cooperation among scholars seeking to examine,explore and explain the behaviour and practices of management within the transforming societies of Central and Eastern Europe.The theoretical interests of the journal areorganisational and management change,Central and East European societies (including those on the fringes of Europe) undergoing processes of transition or transformation, andscientific issues of business, management and organisation that arise in such contexts.The JEEMS aims to attract social scientific contributions from scholars of any nation and region, but particularly wishes to encourageauthors from those countries directly experiencing transformational change. Its potential readership is international, comprising academicsand practitioners with an involvement or interest in the management of change in transforming societies in Central and Eastern Europe.